The Relationship of Perceived Reality of Sinetron Anak Jalanan and Anti Social Behavior - Sri Widowati Herieningsih; Tandyo Pradekso (Bina Nusantara University, 2017)
The research was conducted to explain a potential link between antisocial behavior and how children made sense of television program, Anak Jalanan. A survey was conducted on 248 children from 10-12 years old in Semarang with a non-random sampling technique. Besides, a correlation technique was used to examine a relationship. The results confirm that perceived reality on the show is related to children’s anti-social behavior. The findings bring about a warning alert to families, communities, and organizations that have concerns about the impact of media on children. They should reunite their efforts to do a more massive movement to make the media content more children-friendly. Parents also need to employ parental mediation at home to reduce the negative impact of such television programs on their children.